A comparison of SHR and Vital Statistics homicide estimates for U. S. cities - Loftin, Colin (Journal of contemporary criminal justice, 2008)
Differences between homicide estimates for large cities from 1987 through 1991 using the Supplementary Homicide Report (SHR) and the National Vital Statistics System (NVSS) are reported. Large differences exist between the NVSS and the SHR estimates expressed both as counts and as rates per 100,000 residents. Three major reasons for the differences are identified. First, many cities fail to report the SHR data in some years during the study. Second, in some places the police jurisdiction used in the SHR does not correspond to the boundaries of the city used in the NVSS. Third, the SHR associates victims with the place where the assault occurs, whereas the NVSS associates victims with the place of residence. For many purposes, the NVSS provides more accurate and appropriate measures of homicide victimization than the SHR. However, because the city-level NVSS data are requested by place of residence, they measure a different concept than the SHR, which classifies victims by place of occurrence.